In silico Docking Reveals Interaction Pattern between Topoisomerase I and Camptothecin Analogs: Implication for Ovarian Cancer Treatment - Nuha, Ulin; Mustofa, Zainul (Proceeding International Conference on Global Resource Conservation, 2015)
Ovarian cancer is one of cancer types that begins in the ovaries. Many kind of anticancer agents are developed for the treatment now. Camptothecin analogs are agent that inhibit the action of DNA topoisomerase I, a nuclear enzyme that relaxes the supercoiled DNA during the replication, recombination, transcription, and repair of DNA. FDA have been approved two camptothecin analogs for the treatment of ovarian and colorectal cancer, those are topotecan and irinotecan. Another analogs are in various stages of clinical development, including 9-aminocamptothecin, rubitecan, lurtotecan, and exatecan mesylate. The purpose of this study is to discover interaction pattern between topoisomerase I and camptothecin analogs through in silico docking. PyRx is used for DNA topoisomerase I and camptothecin analogs docking. The interactions between topoisomerase I and camptothecin analogs were visualized and analyzed using PyMol and LigPlus. Our results show that the binding pattern between another camptothecin analogs, including rubitecan, lurtotecan, and 9-aminocamptothecin, with DNA topoisomerase I is relative similar with irinotecan-DNA topoisomerase I complex, specifically in the binding of Arg364, Asn491, Lys493 and Lys532.6Â Keywords: camptothecin analogs; in silico docking; interaction pattern; ovarian cancer; topoisomerase I